2021
DOI: 10.18805/ag.r-2221
|View full text |Cite
|
Sign up to set email alerts
|

Post Harvest Applications of Cold Plasma Technology: A Review

Abstract: Plasma is the fourth state of matters which have a wide application in food processing and post harvest technology. Plasma when applied over crops has tremendous effects in improvement in the quality and other post harvest attributes. Application of cold plasma technology could effectively induce desirable changes in its overall quality and diverse physiology. The following review would discuss the application of non-thermal plasma technology to disinfect and decontaminate processed food product and fresh hort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These physiological changes may be desirable or undesirable depending on the type of produce as these changes directly affect eating quality. UV-C treatment has been shown to enhance antioxidant systems for both antioxidant compounds and oxidative enzyme activities in various fresh produce pear [75], mangosteen [76], mangoes [78], broccoli [83,84], leaf vegetables [85], garlic [86], pepino fruit [87], and tomato [88,89]. While many studies have shown that UV-C radiation treatment can induce many bioactive compounds, but some studies have shown that UV-C treatment did not enhance polyphenols, β-carotene, ascorbic acid, chlorophyll contents in persimmon and cucumber [90], and total phenolic content, anthocyanin compounds, and antioxidant activity in grape [81].…”
Section: Uv-c Treatment In Postharvest Nutritional Valuesmentioning
confidence: 99%
See 4 more Smart Citations
“…These physiological changes may be desirable or undesirable depending on the type of produce as these changes directly affect eating quality. UV-C treatment has been shown to enhance antioxidant systems for both antioxidant compounds and oxidative enzyme activities in various fresh produce pear [75], mangosteen [76], mangoes [78], broccoli [83,84], leaf vegetables [85], garlic [86], pepino fruit [87], and tomato [88,89]. While many studies have shown that UV-C radiation treatment can induce many bioactive compounds, but some studies have shown that UV-C treatment did not enhance polyphenols, β-carotene, ascorbic acid, chlorophyll contents in persimmon and cucumber [90], and total phenolic content, anthocyanin compounds, and antioxidant activity in grape [81].…”
Section: Uv-c Treatment In Postharvest Nutritional Valuesmentioning
confidence: 99%
“…Plasma is commonly known as the fourth state of matter, after gases, liquids, and solids. Plasma is quite like a gas than a solid or liquid, but its property differs from solid, liquid, and gas [86]. Two major types of plasma are differentiated based on thermodynamics: thermal plasma and non-thermal plasma (referred to cold plasma, temperature < 60°C) [86][87][88].…”
Section: Plasma Technology 61 Types Of Plasma and Plasma Generationmentioning
confidence: 99%
See 3 more Smart Citations